Kajian Sosiologi Ian Watt dalam Film “Anak Karaeng” Karya Yus Amin DB - Fadil, Ahmad; Putri, Aryuni; Hasibuan, Tri Marsha (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to analyze the relationship between writers, literary works, and society in the film Anak Karaeng. This film raises the theme of the customs of Kakaraengang (nobility) in Makassar society, especially in Takalar Regency. This study uses the Ian Watt model of literary sociology approach which focuses on three aspects, namely: the author's social context, literature as a reflection of society, and the social function of literature. This type of research is qualitative using a descriptive method that describes the form of literary sociology. This study uses interactive model data analysis with research analysis techniques according to Miles & Huberman (1994). The results of this study indicate that the social context of the author of the film Anak Karaeng is influenced by his cultural background and experience in working on previous films. This film reflects the social reality of Makassar society which still adheres to the customs of Kakaraengang, which triggers conflict in interpersonal relationships. This film also has a social function as a medium of education and entertainment for the community, as well as a reflection of the culture and traditions of the Makassar tribe.